(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2022)
COVID-19 has a very cataclysmic impact on the world's panoramic view of human well being in terms of healthcare and management. The COVID-19 Infection with an increasing number of patients has not only affected the physical but also the mental state of society. The symptoms manifested by COVID-19 range from fever, malaise, myalgia, headache, to respiratory system symptoms of cough, stuffy/runny nose, and difficulty breathing. The novel coronavirus is known to affect the central nervous system, producing critical and some long-lasting neurological concerns. It has an impact on the pre-existing mental and affective ill patients as well as healthy individuals with anxiety, worrying, and panic symptoms, and fear conditioning, which has become a big concern. Although COVID-19 is a respiratory infection and the cardiovascular event is the main cause of fatality, medical professionals must understand its neurological complications to reduce the mortality rate in infected patients. Further research on specific risk factors or determinant protective factors from the neurological symptoms is needed to reduce the risk of complication in COVID-19 infection cases. This review highlights the possible pathogenesis and mechanisms of invasions with the associated Neurological impacts like GBS, encephalitis and meningitis based on various case reports and research articles to date.